Islamophobia, Euro-Islam, Islamism, and Post-Islamism: Changing Patterns of Secularism in Europe (American Journal of Islam and Society, 2013)
Modern secularism, as theorized by such prominent liberal philosophers as John Rawls and Jürgen Habermas, prescribes that the state should treat all religions equally on the condition that they and their adherents relinquish their theocratic aspirations and recognize the political sovereignty and superiority of man-made law. Convinced that the secular bargain undermines the moral virtue of society and its members, a small, fragmented, but nevertheless conspicuous number of Islamists in Europe prefer to observe Islamic law in all walks of life, private and public. Alarmed by Islamists and informed by Orientalist readings of Islam, an increasingly vehement and vociferous contingent of Islamophobes avers that Islam is inherently incompatible with democracy and urges European governments to treat neither Islam nor Muslims equally, but rather suspiciously as real or potential threats to the wellbeing of European societies. In contrast, advocates of Euro-Islam insist that Islam can be reformed, like Christianity, to meet the requirements of modern secularism. This article contends that elements of all three of these vying ideological positions have found their way into policymaking targeting Muslims in several European lands. The resulting inconsistency and contradiction – what I call policy “messiness” – corroborate the process of “mutual fragilization” theorized by Charles Taylor, in which actors facing radical value pluralism develop solicitude regarding their own principles as well as greater tolerance for ambivalence. The latter, in particular, creates what Homi Bhabha terms a “third space” from which actors confronting cultural pluralism can freely and constructively explore cross-fertilizations and hybrid combinations with the potential to yield yet unimagined approaches and solutions to the problems of “super-diversity.” I identify just such a creative hybridity among a younger generation of European Muslims whom many observers dub “post-Islamists.”